Probing Higgs couplings in e(+)e(-)->gamma gamma gamma - deCampos, F.; Lietti, S. M.; Novaes, Sérgio Ferraz [UNESP]; Rosenfeld, Rogério [UNESP] (Elsevier B.V., 1996)
We investigate the existence of anomalous Higgs boson couplings, H gamma gamma and HZ gamma, through the analysis of the process e(+)e(-) gamma gamma gamma at LEP2 energies. We suggest some kinematical cuts to improve the signal to background ratio and determine the capability of LEP2 to impose bounds on those couplings by looking for a Higgs boson signal in this reaction.